Multipel Simultan Perdarahan Intraserebral pada Gangguan Ginjal - Debora P. Pernanda Saragih; Rashellya Rasyida; Maula Gaharu (Journal of Comprehensive Science, 2026)
Simultaneous multiple intracerebral hemorrhage (MSPIS) is a very rare condition with an incidence of only 2% of hemorrhagic strokes and a worse prognosis than single hemorrhage. Reporting a series of cases of MSPIS and analyzing the association of renal impairment with the pathophysiology of MSPIS through the mechanism of cerebral amyloid angiopathy. This descriptive study is a report of two cases of MSPIS in patients with renal impairment who underwent CT scan of the head without contrast. Case 1 (female, 56 years old) with decreased consciousness, seizures, blood pressure 180/100 mmHg, GCS 10, urea 262 mg/dL, creatinine 5.2, GFR 9 mL/min/1.73m², was found to have hemorrhage in the right parietal lobe and cerebellum; the patient died in the second week. Case 2 (male, 54 years old) with balance disorders, blood pressure 250/120 mmHg, urea 113 mg/dL, creatinine 5.6, GFR 11 mL/min/1.73 m², was found to have hemorrhage in the right parietal lobe and left thalamus; the patient was discharged with stroke sequelae. Renal impairment plays a role in the occurrence of MSPIS through vascular remodeling, impaired autoregulation, and increased ?-amyloid deposition due to decreased excretion and dysfunction of A?-degrading enzymes. Renal function screening in patients with stroke risk factors is needed, as well as further studies with larger samples to understand the molecular mechanisms of MSPIS